Future Anxiety Among College Students in A – Jalil Region in Light of Some Variables - Al-Momani , Mohammed; Naeem, Mazen (Jordan Journal of Educational Sciences, 2013)
The purpose of this study is to investigate future anxiety among college students in A – Jalil Region in light of some variables. To achieve the aim of this study the researchers developed a questionnaire about future anxiety; the study sample consisted of (47) items distributed into five domains and administrated to the study sample consisted of (439) male and female students randomly chosen (208 males, 232 females).The findings of the study showed that the level of future anxiety among the study sample was high , and the economic domain came first in a high degree, while the family domain came in the final rank with a high degree too. Moreover, the findings showed that there were no significant statistical differences in the level of the total future anxiety among the sample due to the differences in major or study level. There were significant statistical differences in the level of total future anxiety due to the differences of gender in favor of males. Meanwhile, there were significant statistical differences in both social and economic fields due to the differences in gender in favor of males. There were significant statistical differences in the work domain due to differences in the study major in favor of scientific majors. Furthermore, there were no significant statistical differences in all domains due to the differences in the study level.